Utilization of midwives service scheme among women farmers in Southwestern Nigeria - JO, Oluwasusi; KA, Thomas; MG, Olujide; YO, Oluwasusi (Journal of Community Medicine and Health Solutions, 2020)
Maternal mortality accounts for most deaths in agrarian communities of Nigeria due to poor access to midwives services and inadequate Skilled Birth Attendants (SBAs). The Midwives Service Scheme (MSS) was established to engage more SBAs and advocate better utilization of pre and post-natal care services. Studies have focused on maternal mortality reduction, however, information on underlying factors that predispose MSS target beneficiaries to its utilization is scarce. Therefore, utilization of MSS among women farmers in southwestern Nigeria was investigated. A four-stage sampling procedure was used. Three states from southwestern states (Oyo, Ogun and Ekiti) were randomly selected. Thereafter, ten Local Government Areas (LGAs) from eighteen LGAs that adopted MSS programme in the selected states were sampled. Also, 30% of the MSS facilities in the sampled LGAs were selected, resulting in 13 MSS facilities. Proportionate sampling technique was used to select 20% of registered women farmers in the selected 13 MSS facilities to give 207 respondents. Interview schedule was used to collect data on respondents’ socioeconomic characteristics, Maternal Health Information Sources (MHIS), Maternal Health Information Seeking Behavior (MHISB) and utilization of MSS. Data were analyzed using descriptive and inferential statistics. About (55.6%) of the respondents had formal education. MHISB and effectiveness of MSS was rated low by 53.2% and 55.6% of the respondents, respectively. MSS was moderately utilized by 64.7% of the respondents. The MSS utilization was 49.24 ± 11.39 (Oyo), 45.08 ± 9.28 (Ogun) and 44.00 ± 10.71 (Ekiti). Respondents’ education (χ2 = 12.85), family size (r = 0.02), monthly income (r = 0.48) related positively and significantly (r = 0.27) to MSS utilization.